SHOOTING FOR THE STARS: CEO AND FOUNDER OF SPACE ENTERTAINMENT COMPANY SHARES HER PASSION WITH USM COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 23 February 2017 The Chief Executive Officer and founder of ALE Co. Ltd, Dr. Lena Okajima from Japan was at Universiti Sains Malaysia (USM) recently to deliver a talk on her childhood passion, which is looking at shooting stars.